2017
DOI: 10.1016/s0140-6736(16)31596-3
|View full text |Cite
|
Sign up to set email alerts
|

Mesh, graft, or standard repair for women having primary transvaginal anterior or posterior compartment prolapse surgery: two parallel-group, multicentre, randomised, controlled trials (PROSPECT)

Abstract: UK National Institute of Health Research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
168
6
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 224 publications
(197 citation statements)
references
References 22 publications
12
168
6
1
Order By: Relevance
“…The results of our study confirm the low rate of recurrence after implantation of an alloplastic mesh for cystocele repair described in the AWMF guidelines compared to conventional anterior colporrhaphy, which has a recurrence rate of up to 30 % [1,25]. In contrast, the recently published PROSPECT study found no benefit for mesh-based procedures compared to conventional methods [26]. They found no significant differences with regard to undesirable events, rates of dyspareunia and recurrence, and the number of repeat operations.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…The results of our study confirm the low rate of recurrence after implantation of an alloplastic mesh for cystocele repair described in the AWMF guidelines compared to conventional anterior colporrhaphy, which has a recurrence rate of up to 30 % [1,25]. In contrast, the recently published PROSPECT study found no benefit for mesh-based procedures compared to conventional methods [26]. They found no significant differences with regard to undesirable events, rates of dyspareunia and recurrence, and the number of repeat operations.…”
Section: Discussionsupporting
confidence: 84%
“…At 12 and 36 months after the procedure, the quality of life of the surveyed study participants had improved even more, and the difference to the preoperative figures remained significant. Further studies have also confirmed that mesh-based correction of pelvic organ prolapse can significantly improve patientsʼ quality of life, despite mesh-associated side-effects [26][27][28][29][30][31].…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…13,14 A recent randomized clinical trial compared mesh and non-mesh transvaginal prolapse repair and found that there was no difference in objective or subjective outcomes, and that 1/10 patients who had mesh-augmented repairs had secondary surgery for mesh complications. 15 Placement of transvaginal mesh may still be indicated in select cases; for example, in the setting of recurrent prolapse in which an abdominal sacrocolpopexy is contraindicated.…”
Section: Cua Position Statement Regarding the Use Of Transvaginal Mesmentioning
confidence: 99%
“…Going back to native tissue repair is clearly not the answer. The Lancet Prolapse Surgery: Pragmatic Evaluation and Randomised Controlled Trials (PROSPECT) [1] proved the futility of surgical intervention to the vagina with >80% failure rate at 6 months and further attrition at 1 year.…”
mentioning
confidence: 99%